Estrangeiros, Vinhos de Viana e Vinhos do Porto (séulos XVII-XVIII) - Cardoso, António Barros (2017)
Viana do Castelo and Oporto were export centers for wines produced in their respective areas of influence. These cities had the links connecting them with the rivers Lima and Douro that facilitated the arrival of such wines to the riverside piers of the respective bars. Therefore, the foreigners, especially the English, had in the structuring of the agro-industry of such wines a prominent role. Many distributed their commercial activity by the two cities and gave name to great brands and companies that, although based in the square of Porto, never stopped to commercialize the Green Wines that began by being called Wines of Viana for exiting by the port of the city capital of Minho.